(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Male subjugation, confined identity, and unpaid labour have been the hallmarks of female identity. The term “feminine” – that is defined as “other” than “masculine” – connotes qualities quite opposite to “masculine.” They are not only binary opposite terms, but the first one also bears all sorts of negative aura. However, Feminists, for the last one century, have been raising their voice against the practice. While Kate Millet in Sexual Politics (1970) registers that sexual politics governed by male chauvinistic views has placed man as a sovereign subject in the society and woman as subjugated to man, Judith Butler in Gender Trouble Feminism and Subversion of Identity (1990) holds that “gender” is just an approval and continuation of the traditionally imposed images. The entire feminist discourse revolves around two axioms i.e. “gender” difference is the basis of structural inequality between male and female, and “gender” inequality is not a biological reality but a cultural construct. It aims to understand the social and psychic mechanism that constructs and perpetuates gender inequality and tries to subvert it to the possible limits.